In Defence of some "Paradoxes" of Trade Theory - Herberg, Horst; Kemp, C. (American Economic Review, 1978)
In recent years there has been a systematic exploration of the implications of relaxing the strict assumptions of the textbook version of the Heckscher-Ohlin theory of international trade. Some of the bestknown propositions have turned out to be highly vulnerable to changes in assumptions. Thus if the assumption of constant returns to scale is relaxed, one must be prepared to sacrifice the Stolper-Samuelson and Rybczynski theorems (see Ronald Jones, 1968, and Kemp), and one must accept the possibility that commodity prices and outputs are negatively associated (see our 1969 paper). And if factor-market distortions are admitted, one must be prepared for the possibility that the ranking of industries by value factor intensities may be opposite to the ranking by physical factor intensities, implying in turn that outputs and prices may be negatively associated and that the Stolper-Samuelson and Rybczynski theorems must be rephrased and then cease to be dual to each other (see our paper with Stephen Magee; Jones, 1971). Against the background of traditional results, the new findings have been viewed as perverse and paradoxical.